The Impacts of Extreme Heat Days on the Prevalence of Domestic Abuse - Kien Le (SAGE Open)
The escalating global temperature, attributed to climate change, has drawn extensive attention due to its far-reaching socio-economic consequences. This study investigates the relationship between extreme heat days and the prevalence of domestic abuse, shedding light on an underexplored dimension of social dynamics. Leveraging comprehensive data from Demographic and Health Surveys and Global Historical Climatology Network, the study utilizes a fixed effects regression framework that capitalizes on the distinctive spatial and temporal variations in temperature patterns and establishes a positive relationship between prolonged exposure to extreme heat and various forms of domestic abuse against women. In summary, each additional day where maximum temperature surpassing 35 degrees Celsius throughout the year, in comparison to the local norm, results in a 0.52%, 1.22%, 0.32%, and 1.26% rise in the composite indices of moderate physical abuse, severe physical abuse, psychological abuse, and sexual abuse, respectively, relative to sample averages. The findings not only advance our understanding of the societal ramifications of climate change but also inform intervention strategies aimed at mitigating the potential escalation of domestic abuse in the context of global warming.